Fortschritte in der physikalisch-geographischen Kenntnis der Antarktis - Loewe, Fritz (ERDKUNDE, 1961)
I A number of publications giving regular progress reports on the exploration of the Antarctic are listed. The outline of the continent has been mapped almost completely. During extensive journeys with mechanically driven vehicles and during flights in the interior some hitherto unknown mountain ranges have been found. The mean height of the continent can be estimated to 2400m; the maximum height of the ice cap reaches 4000 m. Geological, gravitational and seismic observations confirm that the continent consists tectonically of two main parts, one a contimation of the Andean chain, the other of the block type of the southern continents. The separating trough between the Ross and Weddell Seas is probably not completely continuous. A considerable part of the rock base of the ice cap lies today below sea level; but it has not the regular bowl shape of the underground of most of the Greenland ice cap. The mean thickness of the antarctic ice is of the order of 2000 m, its mass 25 million cbkm. The maximum thickness is 4250 m. The thickness of the big ice shelves increases towards the interior. Deep bore holes in the ice show to a depth of 300 m unexpectedly no increase of temperature with depth. This may be caused by the motion of the deeper ice from higher and colder regions or by a change of climate. The mean annual accumulation on the ice cap can be estimated to 10-13 cm water equivalent. At present the loss of substance in the border regions does not seem to equal the accumulation. Whether the surplus can be removed by melting on the under-side of ice shelves, is doubtful. Meteorological observations reveal in the interior extremely low temperatures. Stations at 78° S near 100° E at about 3500 m have an annual mean temperature of – 55° with extremes to -88°. The South Pole has a mean of – 49°. The decrease of temperature with height exceeds 1?/100 m. Notwithstanding very strong solar radiation in midsummer the antarctic continent is a strong sink of heat, mainly on account of the very high albedo of the snow cover. The big temperature gradient from the interior to the border might contribute to the stronger general circulation of the southern hemisphere. In earlier periods, with a bigger extent of ice caps on the northern hemisphere, the relation between the two hemispheres might have been reversed.